Thinking at the speed of bias how to shift our unconscious filters - Taylor, Sara (Ascent Audio, 2024)
Respected DEI expert Sara Taylor presents a down-to-earth guide on how to tackle unconscious biases and foster true equity in our rapidly changing world. Through relatable examples and practical strategies, listeners learn to deliberately slow down their thought processes and become aware of their filters in various situations. Taylor encourages listeners to question their own assumptions by asking, "Do I know that what I'm thinking is actually true?" and "Why might I be reacting this way?" The book demonstrates the importance of a clear set of competencies, skills, and strategies for addressing unconscious bias. By developing a culturally competent mindset and using a shared, holistic language to discuss these issues, listeners gain the tools to understand, discuss, and implement change both at home and in the workplace. This approach avoids blame or shame, making it accessible and empowering for everyone. The book's insights extend beyond individuals; it demonstrates how organizations can scale up cultural competence to transform their structures and systems. With a strong sense of hope, listeners are empowered to make a difference, creating a more just and equitable world for all.
Online resource; title from title details screen (O'Reilly, viewed September 10, 2024)
Keywords: Prejudices; Discrimination; Multiculturalism; Organizational change; Préjugés; Multiculturalisme; Changement organisationnel; multiculturalism; Audiobooks; Livres audio